Corporate Social Responsibility, Board Gender Diversity, and Corporate Financial Performance - Rona Larasati; Tastaftiyan Risfandy (Universitas Muhammadiyah Pontianak, 2026)
This study examines the effect of Corporate Social Responsibility (CSR) on corporate financial performance and the moderating role of women on boards among ASEAN-5 non-financial firms. Using panel data from 115 listed companies (1,265 firm-year observations) during 2014–2024, the study employs panel regression with Random Effects and Fixed Effects models. The results show that CSR significantly improves both accounting-based (ROA) and market-based (Tobin’s Q) financial performance. However, women on boards weaken the positive CSR–performance relationship. These findings highlight the importance of balancing CSR investment and board gender diversity to maximize corporate value.